2017
DOI: 10.1177/1559325817744451
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis and Homeopathy: Toward a New Self-Consciousness

Abstract: Contrary to common belief, most new discoveries and theories are not merely additions to the existing stockpile of scientific knowledge; in order to assimilate them, the scientist usually has to rearrange his intellectual mind, discarding elements of his own previous theories. In this sense, he plays the role of a divergent thinker since the scientific community is often not ready to accept a new position for many reasons, among which not only lack of flexibility and open-mindedness but also political and econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(50 reference statements)
0
4
0
Order By: Relevance
“… 9 - 12 To our knowledge, this is because a simple and direct “activity” based molecular mechanistic explanation is lacking. Therefore, several “mainstream scientists” deem hormesis to be a “marginal science” in cellular physiology, owing to its “proximity to homeopathic ideas.” 13 …”
Section: Introductionmentioning
confidence: 99%
“… 9 - 12 To our knowledge, this is because a simple and direct “activity” based molecular mechanistic explanation is lacking. Therefore, several “mainstream scientists” deem hormesis to be a “marginal science” in cellular physiology, owing to its “proximity to homeopathic ideas.” 13 …”
Section: Introductionmentioning
confidence: 99%
“…It is known that even at concentrations beyond Avogadro's number (10 −24 M), high dilutions of many drugs can modulate gene expression in biological systems, though in a non-linear manner. 54 55 56 From a more comprehensive point of view, the balance of functions in the different tested conditions combining the LPS challenge with varying kinds of aspirin preparations suggests the triggering of different levels of the hormesis process, which is one of the hallmarks of health and cell adaptation. 57 Indeed, the results demonstrated that Aspirin 15cH could induce the organization of macrophage pseudopods in a very particular way and reduced the cell contingent able to express TLR-4 on the cell surface, which is a phenotype compatible with M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Studies have proven the effects of homoeopathic medicine superior than placebo and had been investigated with ethanol issues in cell culture experiments, ethanol toxicity in animal experiments and drug delivery (pharmacokinetic and pharmacodynamics) activity through hormesis effects. (6) Inspite of so many rigours efforts putforth by various researchers in deciphering the actions of placebo against homoeopathy, still researchers are reluctant to accept its scientific evidence and are attempting in proving homoeopathy as placebo (pseudo-science) and not merely as therapeutic science. (7) Today, there are so many pooled clinical trial investigated on homoeopathy by considering the Evidence Based Medicine Criteria.…”
Section: Placebo and Homoeopathy: Entangled Approach In Research Prac...mentioning
confidence: 99%